ANALISA K RUSAKAN SISTEM MEKANIS PADA AUTOMATIC SLIDING DOOR DI SHELTER KALAYANG TERMINAL 2 BANDARA INTERNATIONAL SOEKARNO – HATTA, CENGKARENG - Kurniawati, Zulina; puji, Annisa; Adria Pradana, M. Faris; Wahyu Christian, Panji; Fadilah, Anugrah; Rama Wijaya, Ferdy (Program Studi Teknik Mekanikal Bandar Udara, 2024)
Soekarno-Hatta International Airport, Cengkareng has an automatic sliding door as supporting equipment for public facilities located in terminals and non-terminals. In the automatic sliding door located in the terminal 2 kalayang shelter, experiencing a slow motion system. It can be seen when there is an object / object passing through the automatic sliding door, what happens to the automatic sliding door itself experiences slow movement when opening and closing, it is feared that the object / object that passes through can be pinched by the automatic sliding door. Therefore it is necessary to find what causes the motion system to experience slow movement when opening and closing the automatic sliding door, so that the automatic sliding door can be operated normally without disturbing the comfort and safety of passengers. Factors that are indicative of the automatic sliding door are caused by mechanical factors. In mechanical factors there are, roller hanger that has been worn, v-belt that has eroded / changed shape, and glass leaves that are not symmetrical